Legal Protection for Patients Participating in Health Insurance Administering Agencies with Heart Disease with Medication Restrictions in Outpatient Services in Hospitals - Suwondo Ariyanto; Mokhamad Khoirul Huda; Asmuni (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
Health is a human right that must be realized in accordance with Pancasila and the 1945 Constitution. BPJS patients have the right to get good health services and medicines according to their diseases, including heart disease. The administration of drugs in the National Health Insurance (JKN) program must be in accordance with the National Formulary (Fornas). There are rules regarding drug restrictions in Fornas that cause problems in outpatient services for BPJS patients with heart disease. The purpose of this research is to analyze the legal protection of patients and the hospital's responsibility for drug restrictions. Research Methods: The type used in this study is normative juridical with a statute approach and a conceptual approach. Collection and processing of legal materials using document studies or library materials with added literature, journals and expert opinions related to legal issues and then read, studied and analyzed to arrive at a conclusion. Results: Legal protection for BPJS patients with heart disease is contained in the 1945 Constitution and the Law on Health in 2023. The hospital is also responsible for BPJS patients to get medicines according to medical examination. Conclusion: BPJS patients with heart disease have legal protection to get optimal therapy and the hospital is responsible for administering restricted heart drugs so that patients get therapy according to the guidelines.